Analisis Lokasi Rawan dan Biaya Kecelakaan Ruas Jalan Bojonegoro-Ngawi KM.33-KM.63 - Ristiyanto, Hartono Guntur (SIMETRIS, 2023)
The Bojonegoro-Ngawi highway KM.33-KM.63 is part of the national road that connects the provinces of East Java and Central Java. One of the strategic roles of this road segment is that it is the closest access to the Trans Java toll road Solo-Kertosono section. Accidents on these roads have the potential to result in a decrease in the performance of these roads, namely in the aspect of road user safety. Therefore, it is necessary to conduct a study of accident-prone areas on this road section. Accident data available at the time the research was conducted was still in the form of tabulation of raw accident data. Information regarding accident-prone locations and costs is not yet available. This information is needed in an effort to improve traffic safety for the prevention and handling of accidents. Based on the background of the problem, the formulation of the research problem is: where are the accident-prone locations and what are the costs incurred? Analysis of accident-prone locations uses the Equivalent Accident Number (EAN) and Upper Control Limit (UCL) methods and the accident cost analysis method uses the Gross Output method. The results of the analysis of accident-prone locations show that there are 12 segments whose AEK values ​​are above the limit value or UCL. The biggest loss in an accident is caused by the death toll. While the largest accident classification costs occur in fatal accidents. Meanwhile, the analysis of accident costs per road segment based on the type of accident victim shows that the top 3 segments with the highest accident costs are identical to the results of the analysis of AEK and UCL values. The limitation of this research is that it has not considered qualitative losses. This method does not include compensation for pain, fear, grief or suffering. Therefore, for further research it is necessary to carry out a more comprehensive analysis regarding the types of material and non-material losses